Sistema informático web para la gestión de cobranza en el CETIC de la Municipalidad Distrital de Punchana, año 2021 - Pacaya Yance, Susan Rebeca (2022)
This investigation raised the objective of developing and implementing a web computer system to improve collection management in the Specialized Center for Information and Communication Technology (CETIC), of the district municipality of Punchana, which has a quantitative approach, the level It is a technological application, according to the intervention of the researcher it is pre-experimental, the number of measurements is cross-sectional and the data planning is prospective, the sample design was taken from the study population, the recording times of the operations carried out to measure the variable dependent on the management processes in the CETIC such as the registration of payments, registration, registration of new personnel and the generation of reports (20, 20, 10 and 10 time records respectively), the data collection method being a specialized stopwatch, the results were largely very satisfactory, achieving an effectiveness in the registration of registrations of 114%, in the registration of personnel 136%, the registration of payments 126% and in the generation of management reports 15,246%, of In this way, the Research Hypothesis is accepted: "If the web computer system is implemented, then the collection management will be optimized in the CETIC, of the district municipality of Punchana, year 2021".